Surface Behavior and Thickness Measurement of Free Standing Thin Film of Liquid Crystal Compound Biphenyl (E7) - Asif Siddiqui,; Zaheer Uddin ,; S. Naseem Shah, (Journal of Basic & Applied Sciences, 2016)
A simple experimental setup based on a polarizing optical technique is designed to find the thickness of free standing thin film of Biphenyl (E7). Monochromatic light is passed through a liquid crystal thin film in two different modes of placement. In each mode approximately 10 mg of Biphenyl is used. The films of varying area were used in this study. The thin films were highly stable and could survive more than one day. The intensity of transmitted monochromatic radiation is measured using this technique by placing thin film in horizontal and vertical modes. Using Beer-Lambert’s Law the thickness of thin film is also measured using polarizing optical technique. In both the modes (horizontal and vertical) different behaviors of thickness of thin film are observed..